Examining The Association Of Inclusion Setting On Academic Performance, Social Interaction, And Self- Esteem Among Students With Hearing Impairment In Saudi Arabia - Sulaiman Mohammed, Alshutwi (2022)
Since the inclusion concept started, there were debates amongst professionals and parents regarding the appropriate educational setting for deaf and hard of hearing (DHH) students. Based on the existing empirical evidence which show that there is a substantial lack of research in the Saudi Arabian context, this study investigated the impact of inclusion settings on academic performance, social interaction and self-esteem of DHH children in Saudi Arabia.